A gazdasági és közigazgatási reformok hatása a területi fejlődésre - Perger, Éva (Tér és Társadalom, 1989)
With reference to the results of Hungarian economics, sociology, political science and geography, the paper calls for a comprehensive approach in geographical research which should rely on there results and attempt to summarize the spatial impacts of the praxis of the organisation of society in ex isting socialism. The author herself does attempt to analyse the impacts of economic and administrative reforms on regional development on the basis of relevant Hungarian literature and the 'reform histories' in three socialist countries. In the first chapter the author theoretically clarifies the relationship between economy, administration and regional development. The second chapter briefly reviews how economic and administrative measures related to each other and to regional development in the history of Hungary and two 'extremist' socialist countries: Yugoslavia and Romania. The third part draws general conclusions from contrasting similarities and dissimilarities between countries. The most important statement here is the following: besides significant differences, there are many common features in the development of the three socialist countries. Balkings in economic and administrative reforms and their contradictions had repercussions on each other and as a result, centralized hierarchical control has remained strong in all three countries. Spatial policy objectives and spatial planning appeared in vain from the mid-1960s: the realization of spatial– and settlement development objectives has been limited, spatial disparities have not diminished to significant extent, moreover, interventions in the natural course of spatial development often led to new spatial tensions.